Application of an integrative approach for municipal solid waste management assessment: towards adopting a conceptual model for efficient and sustainable solid waste management. - Adati Ayuba, Kadafa; Abd Manaf, Latifah; Sulaiman, Wan Nor Azmin; Abdullah Ho, Sabrina (IISTE, 2013)
Solid waste management is a global issue that is a growing source of concern in develop and developing countries due to increasing urbanization, changes in consumer pattern and industrialization, which all directly influence solid waste generation. Solid waste is fast becoming an environmental hazard with its management overwhelming the capabilities of the local authorities, which in most countries are responsible for solid waste management. Solid waste management systems vary in most countries with factor that influence each system, as a result different countries adopt different systems with assessments and modifications to suit. This paper assesses solid waste management in FCT Abuja and Putrajaya in a comparative and correlative approach towards adopting a model to suit FCT Abuja with the aim of improving solid waste management in the state.